2002
DOI: 10.1542/peds.110.3.e35
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Adherence to the Zidovudine Regimen for HIV-Exposed Infants to Prevent HIV Infection: A Preliminary Study

Abstract: ABSTRACT. Objective. To describe the extent of adherence to the recommended neonatal zidovudine (ZDV) regimen administered to infants who have been exposed to the human immunodeficiency virus (HIV) to prevent mother-to-child transmission of HIV and to determine which maternal factors are associated with compliance.Methods. HIV-infected women (n ‫؍‬ 87) who were participating in a larger study of perinatal transmission at 3 inner-city New York City hospitals were interviewed 2 to 6 weeks' postpartum to assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
0
12
1
4
Order By: Relevance
“…5,6 One recent study of frequently hospitalized urban residents found diagnoses of substance use and mental illness to be strong predictors of fragmented care and admissions to multiple, unrelated facilities. 7 The majority of studies examining risk factors associated with frequent hospital admissions focus only on patients with specific diagnoses such as HIV, congestive heart failure or psychiatric disease, or in specific age ranges such as infants or the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 One recent study of frequently hospitalized urban residents found diagnoses of substance use and mental illness to be strong predictors of fragmented care and admissions to multiple, unrelated facilities. 7 The majority of studies examining risk factors associated with frequent hospital admissions focus only on patients with specific diagnoses such as HIV, congestive heart failure or psychiatric disease, or in specific age ranges such as infants or the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction with support was found to mediate the relationship between adaptive coping and psychological distress in a sample of Hispanic and African-American women (Simoni, Demas, Mason, Drossman, & Davis, 2000). Disclosure has been related to the availability (Moneyham et al, 1996) and frequency (Simoni et al, 2000) of social support in samples of seropositive women and to adherence among samples of infected mothers for their own treatment (Mellins et al, 2002) and for postnatal prophylaxis of the exposed infant (Demas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Participação em programas de prevenção 13,16,[18][19][20][23][24][25][26][27][28] Acolhimento da equipe de saúde 11,16,21,24 Educação em saúde 20 Conforto das condições de saúde 24 Divulgação do estado sorológico [16][17][18][19] Aderir às medidas de profilaxia da TV 11,[16][17][18][19] Repercussões na saúde sexual 13 Deus e a fé 15,24,27 Divulgação do estado sorológico 29 Motivação para aceitar o diagnóstico e o tratamento 24 repercussões na saúde sexual: consideraram-se com maior capacidade para negociar o planejamento familiar, além do uso de preservativo, e solicitar ao companheiro que realizasse o teste de anticorpos do HIV.…”
Section: Suporte Instrumentalunclassified
“…Quanto à categoria suporte social emocional, observaram-se como fontes a família, 12,14,15,24,25,[27][28][29] o companheiro, 10,22,26 os amigos 15,24,27 e a crença em Deus e a fé, 15,24,27 como estímulos para continuidade do tratamento. Fica explícito que as questões culturais e familiares influenciaram nas decisões em relação aos cuidados de saúde maternos e infantis.…”
Section: Fontes E As Repercussões Do Suporte Social Emocionalunclassified
See 1 more Smart Citation